Wykonaj mnożenie:
a)2(a+b)=
b)-3(x+y)=
c)-5(m-n)=
d)-6(-c-d)=
e)1/2(4x-2)=
f)-2/3(6a-12b)=
g)(c-2d)*(-0,5)=
h)(x²+3y²)*(-1,2)=
Zamień iloczyny na sumy:
a)-4(a+2b-4c-1/2d+1/8m)=
b)-2/5(10x-20y+0,5z-35)=
c)-(1 1/3m-8n+2/3k-16z)*3/4=
d)(20x-15y+2/3z-5/6p)*(-0,3)=

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T17:51:19+01:00
A. 2a+2b
b.-3x-3y
c.-5m+5n
d.6c+6d
e.2x-1
f.-4a+8b
g.-0.5c+1d
h.-x²+2x²-3y²+6y²

zad2
a.-4a-8b-16c+2d-½m
b.-4x+8y-0.2z+14
c.-(1m-6n+½k-12z)= -1m+6n-½k+12z
d.-6x-4.5y-0.2z-0.25p
2010-02-02T17:54:01+01:00
1.
a)2a+2b
b)-3x-3y
c)-5m+5n
d)6c+6d
e)2x-1
f)-4a+8b
g)-0,5c+d
h)-1,2x²-3,6y²

2.
a) -4a-8b+16c+2d-1/2m
b) -4x+8y-1/5z+14
c) (-11/3m+8n-2/3k+16z)*3/4=-11/4m+6n-1/2k+12z
d)-6x+4,5y+1/5z+1/6p
2010-02-02T22:55:16+01:00
Zad 1.
a)2a+2b
b)-3x-3y
c)-5m+5n
d)6c+6d
e)2x-1
f)-4a+8b
g)-0,5c+d
h)-1,2x²-3,6y²

Zad 2.
a)-4(a+2b-4c-1/2d+1/8m) = -4a-8b+16c+2d-½m
b)-2/5(10x-20y+0,5z-35) = -4x+8y-0,2z+14
c)-(1 1/3m-8n+2/3k-16z)*3/4 = -(m-6n+½k-12z) = -m+6n-½k+12z
d)(20x-15y+2/3z-5/6p)*(-0,3) = -0,6x+4,5y-0,2z-0,25p